2018
DOI: 10.1111/asj.13055
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between ultimate pH and antioxidant enzyme activities and gene expression in pork loins

Abstract: Ultimate pH (pH ) is a major determinant factor of meat quality. In this study, we investigated the effects of pH on the muscle antioxidant capacity, and the relationship between pH and muscle antioxidant capacity of pigs. A total of 137 pigs from three pig breeds with the same feeding condition were slaughtered and used to measure the pH , superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), total antioxidant capacity (T-AOC), and malondialdehyde (MDA) content, and gene expression of SOD1 and GPX4. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Thiols occupy a special place among tissular antioxidants due to their following features: (1) extremely high reactivity to sulfhydryl groups, giving thiols the ability to oxidate with exceptionally high speed; (2) oxidation reaction reversibility of sulphhydryl groups to disulphade ones, which presumes the ability of the most energetically favorable thiol antioxidants to keep homeostasis in a cell without their biosynthesis activation; (3) ability of thiols to act as both antiradical and antiperoxile; (4) the hydrophilic nature of thiols provides their high content in the cell’s aqueous stage and gives them the possibility to be defended from oxidative damage of biologically important hydrophilic molecules, including hematoglobuli, and also due to the fact that thiols contain nonpolar groups, and are able to exhibit antioxidant activity even in the lipid phase of the cell [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiols occupy a special place among tissular antioxidants due to their following features: (1) extremely high reactivity to sulfhydryl groups, giving thiols the ability to oxidate with exceptionally high speed; (2) oxidation reaction reversibility of sulphhydryl groups to disulphade ones, which presumes the ability of the most energetically favorable thiol antioxidants to keep homeostasis in a cell without their biosynthesis activation; (3) ability of thiols to act as both antiradical and antiperoxile; (4) the hydrophilic nature of thiols provides their high content in the cell’s aqueous stage and gives them the possibility to be defended from oxidative damage of biologically important hydrophilic molecules, including hematoglobuli, and also due to the fact that thiols contain nonpolar groups, and are able to exhibit antioxidant activity even in the lipid phase of the cell [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pH 24 h post-mortem is an important characteristic and has been reported to influence drip loss, color, and lipid peroxidation. The SOD and GSH-Px activity and T-AOC content were positively correlated to pH 24h post-mortem and an opposite trend of MAD ( Wang et al, 2018 ). Pigs fed 130 mg Cu/kg as hydroxychloride source had an increase in the activities of ceruloplasmin and SOD in serum compared with those that received CuSO 4 on d 30 ( Zheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that oxidative stress can speed up the drop in the pH of meat, and increase the lightness and drip loss of postmortem ( Chen et al, 2017 ; Wang et al, 2017 ; Markovic et al, 2018 ; Wang et al, 2018 ). In this study, dietary supplementation of keratinase at both doses of 100,000 U/kg and 200,000 U/kg have a better redox status, indicated by higher GPX activity and lower MDA concentration, than those of the control.…”
Section: Disscussionmentioning
confidence: 99%